Low Use of Statins in Patients with Acute Myocardial Infarction: A Single Center Experience - 殷偉賢(Wei-Hsian Yin); 王鑑忠(Jiann-Jong Wang); 任勗龍(Hsu-Lung Jen); 江孟橙(Meng-Cheng Chiang); 黃文彬(Wen-Pin Huang); 馮安寧(An-Ning Feng); 楊永年(Yung-Nien Yang); 林昌琦(Chang-Chyi Lin); 楊茂勳(Mason Shing Young) (Acta Cardiologica Sinica, 2007)
Background: Current guidelines recommend that patients with acute myocardial infarction (AMI) should be discharged on statin therapy. However, little data are available regarding the usage of statin in AMI patients in real-world practice. The present study investigated the current status of statin use and the effect of continuous statin treatment on clinical outcomes in patients with AMI. Methods and Results: Three hundred and twenty-five patients (aged 62±13 years, M/F=258/67) with AMI were enrolled. The administration of statin therapy was at the discretion of the treating physician. Patients were classified into 2 groups: patients receiving continuous statin therapy, defined as at least 85% of statin intake throughout the whole study period (adherent group, n = 167, 51%) and patients not taking continuous statin therapy (nonadherent group, n=158, 49%). Continuous statin therapy was independently associated with a reduction in the risk of adverse clinical outcomes (38% versus 68%; P＜0.0001). By Cox proportional hazard analyses, the adjusted odds ratio for the development of adverse events in the adherent group compared with the nonadherent group was 0.56 (95% CI, 0.32 to 0.97, P=0.039). Conclusion: Continuous statin therapy may reduce the risk of adverse clinical outcomes after AMI. However, the relatively low use of statin in the study patients indicates that there remains substantial room to improve implementation of statin therapy to AMI patients in real-world practice.